Oscar F. Greene, Revised Ordinances of the City of Boulder, Colorado 157, § 511 (1899) - (:unkn) unknown (My University, 1899)
Prohibited carrying any gun, pistol, revolver, or other firearm into any parks, or shooting any firearms in any parks. Violators guilty of a misdemeanor.
Keywords: CARRY - SENSITIVE PLACES